Analisis Alasan Turki Melakukan Pembelian Senjata S-400 Rusia - Sinaga, Indah; Parameswari, A.A Ayu Intan; Suwecawangsa, Adi (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
This research aims to explain Turkey's reason for purchasing Russian S-400 missile weapons in 2017, amidst its existence as a member of NATO and must be faced with CAATSA sanctions. Turkey’s decision to purchase S-400 Russia Missile weapons is classified as a unilateral act which actually violates the alliance agreement with the United States. While, on the other hand, the realization for joining the purchase of Russian S-400 Missile weapons seen necessary to make a huge influence in relation to Turkish and Russian relations in the future. Therefore, this Thesis will try to answer the question: "What is the reason for Turkey to purchase Russian S-400 weapons?. With balance of Threat theory, this research is trying to explain the existence of threats that arise from Russia which causes Turkey to decide to purchase S-400 weapons. Cooperation with Russia is seen as a way to inhibit and moderate Russia's future threats. Keywords : Balance Of Threat, Turkey, Russia